Potentials and challenges of implementing Islamic wealth management in Jigawa State, Nigeria - Ahmad Azrin, Adnan; Baba Uba, Ibrahim; Kabiru Uba, Ibrahim (2019)
Islamic Wealth Management is being recognized worldwide, adopted by Muslims and even some non-Muslims globally. Nevertheless, Jigawa State seems to be outdistanced in this regard, despite the fact that it is a Muslim dominated society. Hence, the paper aims at pointing out the potentials for such a Muslim community to strive in actualizing, formalizing and implementing the system in their economic activities and proposing on overcoming the challenges thereof. The study adopts a qualitative approach using a descriptive survey design and document analysis method to analyze relevant literature and identify the challenges of the implementation in Jigawa State, Nigeria. The study found out that there are a lot of challenges which need to be tackled with public awareness on the importance and benefits of the system and the religious obedience in the practice and also the actualization of proper and relevant regulations and regulatory bodies in compliance with the Shari’ah. The study recommends that authorities ought to endeavor to address the national administrative difficulties. Also the open doors flourish for the development and advancement of Islamic wealth management in Jigawa State, Nigeria should be emphasized.